2021
DOI: 10.3389/fimmu.2021.752643
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Immune-Related Gene Signatures in Lung Adenocarcinoma and Lung Squamous Cell Carcinoma

Abstract: Accumulating evidence indicates that immunotherapy helped to improve the survival and quality-of-life of patients with lung adenocarcinoma (LUAD) or lung squamous cell carcinoma (LUSC) besides chemotherapy and gene targeting treatment. This study aimed to develop immune-related gene signatures in LUAD and LUSC subtypes, respectively. LUAD and LUSC samples were divided into high- and low-abundance groups of immune cell infiltration (Immunity_H and Immunity_L) based on the abundance of immune cell infiltrations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 57 publications
1
20
2
Order By: Relevance
“…Generally, the nomogram exerted a medium accuracy on predicting OS of LUSC, displaying a better overall net benefit than the T, N stating system for predicting 1-and 3-year OS rate. Although in terms of validity, this ATIRE-based nomogram did not display a superior performance compared to previously published gene-expression-based nomograms as shown by the Harrell's C-indexes, given an amount of gene-expression-based nomograms exerted Harrell's C-indexes ranging from 0.65-0.85 [44][45][46][47][48][49]. However, in terms of determination reliability, quantification of AITRE level is more stable and reliable than that of gene expression.…”
Section: Discussioncontrasting
confidence: 68%
“…Generally, the nomogram exerted a medium accuracy on predicting OS of LUSC, displaying a better overall net benefit than the T, N stating system for predicting 1-and 3-year OS rate. Although in terms of validity, this ATIRE-based nomogram did not display a superior performance compared to previously published gene-expression-based nomograms as shown by the Harrell's C-indexes, given an amount of gene-expression-based nomograms exerted Harrell's C-indexes ranging from 0.65-0.85 [44][45][46][47][48][49]. However, in terms of determination reliability, quantification of AITRE level is more stable and reliable than that of gene expression.…”
Section: Discussioncontrasting
confidence: 68%
“…Furthermore, we compared the performance of the present signature with those of the other previously reported gene signatures in LUSC. The RMS curve showed that the performance of the present signature was similar to that of the other four signatures ( Supplementary Figure S3C ) ( Huang et al, 2021 ; Li et al, 2021 ; Li et al, 2022 ; Zhai et al, 2022 ). These results suggest that the CSRG signature can serve as a candidate prognostic biomarker for survival in patients with stage I–III LUSC.…”
Section: Resultssupporting
confidence: 57%
“…The most frequent histological subtype of lung cancer corresponds to LUAD, while the minority correspond to LUSC. Recent studies are shedding light into the numerous differences between them that would require the identification of biomarkers of response with discriminating values for each histology independently ( 47, 62, 63 ). Indeed, plasma FKN had positive predictive value only for LUAD treated with ICB in our discovery cohort.…”
Section: Discussionmentioning
confidence: 99%